A new tip correction for actuator line computations - Kaya Onur Dağ; Jens Nørkær Sørensen (Wind Energy, 2020)
Abstract The actuator line method (ALM) is today widely used to represent wind turbine loadings in computational fluid dynamics (CFD). As opposed to resolving the whole blade geometry, the methodology does not require geometry‐fitted meshes, which makes it fast to apply. In ALM, tabulated airfoil data are used to determine the local blade loadings, which subsequently are projected to the CFD grid using a Gaussian smearing function. To achieve accurate blade loadings at the tip regions of the blades, the width of the projection function needs to be narrower than the local chord lengths, requiring CFD grids that are much finer than what is actually needed in order to resolve the energy containing turbulent structures of the atmospheric boundary layer (ABL). On the other hand, employing large widths of the projection function may result in too large tip loadings. Therefore, the number of grid points required to resolve the blade and the width of the projection function have to be restricted to certain minimum values if unphysical corrections are to be avoided. In this paper, we investigate the cause of the overestimated tip loadings when using coarse CFD grids and, based on this, introduce a simple and physical consistent correction technique to rectify the problem. To validate the new correction, it is first applied on a planar wing where results are compared with the lifting‐line technique. Next, the NREL 5‐MW and Phase VI turbines are employed to test the correction on rotors. Here, the resulting blade loadings are compared with results from the blade‐element momentum (BEM) method. In both cases, it is found that the new correction greatly improves the results for both normal and tangential loads and that it is possible to obtain accurate results even when using a very coarse blade resolution.